Dyspareunia. Etiology and therapeutic management. - Enrique Ramón Arbués; Marta Sánchez Gil; Myriam Martín Castillo; Verónica Paredes Rubio; Natalia Barrio Forné; María Torres de Sebastián (Fundación para el Desarrollo de la Enfermería, 2013)
Nowadays sexuality is a domain over scales measuring quality of life of women and is part of her overall health. Thus midwives as professionals responsible for ensuring sexual health of women we must be committed to this area of knowledge in general and the repertoire of sexual dysfunction that may occur along the life cycle of women, to provide her an holistic care.